A combination of 5-azacytidine and nivolumab is a potentially effective rescue therapy in relapsed/refractory AITL - Ricard, Laure; Cervera, Pascale; Stocker, Nicolas; Corre, Elise; Van de Wyngaert, Zoé; Banet, Anne; Marjanovic, Zora; Dulery, Rémy; Bravetti, Clotilde; Joly, Anne-Christine; Baylatry, Minh Tam; Coppo, Paul (Frontiers in Immunology, 2024)
Angioimmunoblastic T-cell lymphoma (AITL) is a peripheral T-cell lymphoma characterized by a T follicular helper cell phenotype expressing PD-1 (programmed cell death-1). AITL exhibits a poor response to conventional chemotherapy, with a median 5-year overall survival of 44 % and a progression-free survival of 32 %. Relapse is common, resulting in a median overall survival of 6 months. Recurrent mutations are detected in genes regulating DNA methylation, including TET2, DNMT3A, and IDH2 variants, along with the prevalent RHOA G17V mutation. In this context, patients treated with the hypomethylating agent 5-azacytidine achieved overall response and complete response rates of 75% and 41%, respectively.We hypothesized that targeted therapies combining anti-PD-1 checkpoint blockers with hypomethylating agents could be efficient in AITL patients and less toxic than standard chemotherapy. Here, we report the efficacy of a regimen combining 5-azacytidine and nivolumab in nine relapsed or refractory AITL patients. This regimen was well-tolerated, especially in elderly patients. The overall response rate was 78%, including four partial responses (44%) and three complete responses (33%). Allogeneic hematopoietic stem cell transplantation was performed in two patients who reached complete response. These preliminary favorable results may serve as a basis for further investigation in prospective studies.1. The combination of 5-azacytidine with nivolumab may provide benefits for patients with relapsed/refractory AITL.2. This combination can serve as a bridge to allogeneic hematopoietic stem cell transplantation. Table 2. Patients' complications on vidaza nivolumab regimen. Infection Cytopenia Other drug-related events Patient #1 2 grade 3 Picc-related bloodstream infections ( Staphylococus epidermidis, Klebsiella pneumoniae)